Phenology and production of traditional seeds of cowpea irrigated with saline water - Torquato Loiola, Aline (Revista Ciência Agronômica, 2021)
Cowpea suffers signifi cant production losses when subjected to salt stress, but the response varies among genotypes. The objective of this study was to evaluate the phenology and production of traditional cowpea seeds under saline water irrigation. The experiment was conducted in two stages, the fi rst one in a greenhouse to evaluate the phenology and production of cowpea genotypes and the second one in the laboratory to assess the viability and vigor of the seeds produced in the fi rst stage. The treatments resulted from the combination of two salinity levels of the irrigation water (0.5 and 4.5 dS m-1) and 14 traditional cowpea varieties (Boquinha, Ceará, Costela-de-vaca, Lisão, Canário, Pingo-de-ouro, Roxão, Branco, Canapum-branco, Canapum-miúdo, Baêta, Coruja, Paulistinha, and Sempre-verde) acquired from traditional farmers in the western region of Rio Grande do Norte, Brazil. Canário, Baêta, and Coruja varieties have a higher number of fl owers per plant and earlier fl owering. Salinity reduced the number of fl owers per plant, increased abortion in all traditional varieties and reduced production in the early varieties Branco, Canapum-miúdo, Baêta, and Coruja. Cultivation under saline water irrigation did not affect the viability of the seeds from the second generation of cowpea, but reduced the vigor of the seeds of the varieties Lisão, Pingo-de-ouro, Roxão, Branco, Canapum-branco, Canapum-miúdo, Baêta and Coruja. The traditional varieties Boquinha, Ceará, Costela-de-vaca, Canário, Paulistinha and Sempre-verde are indicated for the production of cowpea seeds under irrigation with saline water.